The Theater and Vygotsky (Research, Society and Development, 2018)
The Higher psychological functions interfere with the processes of internalisation and psychological development of the individual. However, this function is not instituted by itself, but by social interaction. With this in mind, theater in the perspective of Lev Vygotsky is then seen as a collective activity that acts in the Zone of Proximal Development, uniting the consolidated learning of each subject with different mediation strategies, creating new ZPDs. As for the methodological aspects, a theatrical workshop was applied, based on the games proposed by Viola Spolin, for approximately 3 hours and a half, with 15 students from the 5th grade (approximate age: 9-11 years) of Elementary School I of the private school Complexo Educacional Parque Dunas, located in the North Zone of Natal, Rio Grande do Norte – Brazil. The results show the role of pedagogical mediation for the development of the children's symbolic and theatrical representation capacities in the school context and the students' abilities regarding imagination and creativity. The study concludes, therefore, that it is extremely important to encourage teamwork and autonomy, which can be provided by the arts, such as theater, which are very rich tools within the classroom and notable for the students' cognitive development.